Approaches to the Management of Synkinesis: A Scoping Review - Zubler, Cédric; Punreddy, Ankit; Mayorga-Young, Danielle; Leckenby, Jonathan; Grobbelaar, Adriaan O. (Facial Plastic Surgery, 2024)
Postparalysis facial synkinesis (PPFS) can develop in any facial palsy and is associated with significant functional and psychosocial consequences for affected patients. While the prevention of synkinesis especially after Bell's palsy has been well examined, much less evidence exists regarding the management of patients with already established synkinesis. Therefore, the purpose of this review is to summarize the available literature and to provide an overview of the current therapeutic options for facial palsy patients with established synkinesis. A systematic literature review was undertaken, following the Preferred Reporting Items of Systematic Reviews and Meta-analyses 2020 guidelines. MEDLINE via PubMed and Cochrane Library were searched using the following strategy: ([facial palsy] OR [facial paralysis] OR [facial paresis]) AND (synkinesis) AND ([management] OR [guidelines] OR [treatment]). The initial search yielded 201 articles of which 36 original papers and 2 meta-analyses met the criteria for inclusion. Overall, the included articles provided original outcome data on 1,408 patients. Articles were divided into the following treatment categories: chemodenervation (12 studies, 536 patients), facial therapy (5 studies, 206 patients), surgical (10 studies, 389 patients), and combination therapy (9 studies, 278 patients). Results are analyzed and discussed accordingly. Significant heterogeneity in study population and design, lack of control groups, differences in postoperative follow-up, as well as the use of a variety of subjective and objective assessment tools to quantify synkinesis prevent direct comparison between treatment modalities. To date, there is no consensus on how PPFS is best treated. The lack of comparative studies and standardized outcome reporting hinder our understanding of this complex condition. Until higher quality scientific evidence is available, it remains a challenge best approached in an interdisciplinary team. An individualized multimodal therapeutic concept consisting of facial therapy, chemodenervation, and surgery should be tailored to meet the specific needs of the patient.
Keywords: facial palsy; synkinesis; systematic review; Bell's Palsy